INFLUÊNCIA DO CICLO MENSTRUAL E DO USO DE CONTRACEPTIVOS ORAIS NO DESEMPENHO AERÓBIO DE CORREDORAS - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2018)
Women have stood out increasingly in the sports scene, being the street running, among other sports, the most sought after one. Therefore, getting to know the influences of the menstrual cycles in the physiological response of the female runners, focusing not just on the professional athletes, has caught attention of the scientific community. In this theme, the aim of this work has been to evaluate the influence of the menstrual cycle as well as the use of oral contraceptives in the aerobic performance of endurance exercises (street running) users. This study is characterized by being transversal and observational, carried out with 22 women in the average age of 31,00 ± 5,1, with average BMI of 22,66 ± 2,5 and body fat of 22,38 ± 3,4 %, split in 3 groups: group 1 - control (n=9) non-runners that didn’t use to have contraceptives, group 2 - runners that didn’t used to have contraceptives (n=6) and group 3 – runners that used to have contraceptives (n=7). After the signing of the free and informed consent, the volunteers were submitted to a prior anamnesis and physical exam. After 8 weeks, they were conducted to tests of VO2 máx. through a 12 min Cooper, as well as answered heath questionnaires (RESTQ-sport, WURSS-21), besides answering to the one concerning the Subjective Effort Perception Scale. On the 4 last weeks of experimental phase, samples of blood from the volunteers were collected in order to determine the hormonal levels (Estradiol and Progesterone) and levels of iron and ferritin. The results obtained showed lower levels of estradiol and progesterone in the G3, group of runner that used to have oral contraceptives, just as was observed a better VO2 max., longer distance covered in the Cooper test, besides showing higher iron concentrations compared to the 2 other groups (Group1 and Group 2). In group 2, group of runners that didn’t used to have oral contraceptives. The iron concentrations were even lower than the one in the luteal phase. However, just the control group (Group 1) had reduction in VO2 max. Any correlation between the quality of life variables and the immune system with the period cycle hasn’t been observed, such as the performance. The effort perception was higher in the luteal phase for all groups studied. Thus, it is concluded that the menstrual period shows influence in aerobic performance, in effort perception, in ferric levels of the runners and non-runners with regular menstrual cycle and the use of continuous oral contraceptives avoid such influences, promoting better performance of the endurance athletes.
Keywords: Ciclo ovariano; performance esportiva; resposta imune; níveis férricos; VO2; mulheres atletas; ovarian cycle; sportive performance; immune response; ferric levels; VO2; athlete women; CNPQ::CIENCIAS DA SAUDE